2020
DOI: 10.3390/e22101171
|View full text |Cite
|
Sign up to set email alerts
|

Shape Effect of Nanosize Particles on Magnetohydrodynamic Nanofluid Flow and Heat Transfer over a Stretching Sheet with Entropy Generation

Abstract: Magnetohydrodynamic nanofluid technologies are emerging in several areas including pharmacology, medicine and lubrication (smart tribology). The present study discusses the heat transfer and entropy generation of magnetohydrodynamic (MHD) Ag-water nanofluid flow over a stretching sheet with the effect of nanoparticles shape. Three different geometries of nanoparticles—sphere, blade and lamina—are considered. The problem is modeled in the form of momentum, energy and entropy equations. The homotopy analysis met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The thermophysical properties of the nanofluids are defined as [50] In the above equations, μ is the dynamic viscosity, ρ is the density, c p is the heat capacitance, L is the wall slip parameter, p is the pressure, k is the thermal conductivity, and φ represents the volume fraction of the nanoparticles. Furthermore, the subscript f indicates the base fluid, nf shows the nanofluids, and np is used for nanoparticles.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…The thermophysical properties of the nanofluids are defined as [50] In the above equations, μ is the dynamic viscosity, ρ is the density, c p is the heat capacitance, L is the wall slip parameter, p is the pressure, k is the thermal conductivity, and φ represents the volume fraction of the nanoparticles. Furthermore, the subscript f indicates the base fluid, nf shows the nanofluids, and np is used for nanoparticles.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…Rashid et al [42] analyzed the effects of nano particulates on the energy transmission and entropy formation of MHD Ag-water nanoliquid flow across an elongating sheet. Alharbi et al [43] reported the kinetics of MHD Darcy flow through an extended impervious sheet while Newtonian and hydrodynamic slip boundary restrictions are applied.…”
Section: Introductionmentioning
confidence: 99%
“…They originated that velocity gets reduced with the parameter of the magnetic effect. Rashid et al 16 applied the homotopy analysis technique to study MHD Ag water nanofluid and heat dissipation through an extended sheet including the shape effect of Ag nanoparticles along with entropy generation. Influence of thermophoresis, radiation, and heat generation on temperature, concentration, and velocity in the appearance of MHD and free stream velocity through a cylinder and they initiated that temperature raises with the growth in thermophoresis parameter, curvature parameter, magnetic parameter, and radiation parameter as inspected by Vinita and Poply 17 .…”
Section: Introductionmentioning
confidence: 99%